ANTITUMOR NAPHTHALENYL BENZAMIDE DERIVATIVES (2016)
14 314 14 Naphthalenyl benzamide derivatives according to formula I are described, wherein Ar is an aryl or heteroaryl group, and R-Rare independently selected from H, halogen, CF, hydroxyl, C-Calkyl, and C-Coxyalkyl, or a pharmaceutically acceptable salt thereof. The naphthalenyl benzamide derivatives can be used for the treatment of cancer in a subject.